2010
DOI: 10.1021/ol102554a
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Asymmetric Synthesis of Axially Chiral Allenylsilanes and Their Application to SE2′ Chirality Transfer Reactions

Abstract: Stepwise application of the Pd-catalyzed S(N)2' reaction and the desilylative S(E)2' reaction to the ambivalent 2-bromo-1-silyl-1,3-dienes provides a novel route to the highly enantioselective construction of tertiary and quaternary propargylic stereogenic centers via axially chiral allenylsilanes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 72 publications
0
23
0
Order By: Relevance
“…Axial-to-central chirality transfer of allenylsilanes to alkynes has also been reported. 69 Electrofilic fluorination of enantioenriched allene 84 with Selecfluor afforded propargylic fluoride 85 in 94% ee in 77% yield (Scheme 36). Reaction of allene 84 with propanal dimethylacetal at −78°C in the presence of TiCl4 gave a (4:1) diastereomeric mixture of homopropargylic methyl ethers 86 in 73% and 94% ee (Scheme 36).…”
Section: Organosilane Reagents As Carbon Nucleophilesmentioning
confidence: 99%
“…Axial-to-central chirality transfer of allenylsilanes to alkynes has also been reported. 69 Electrofilic fluorination of enantioenriched allene 84 with Selecfluor afforded propargylic fluoride 85 in 94% ee in 77% yield (Scheme 36). Reaction of allene 84 with propanal dimethylacetal at −78°C in the presence of TiCl4 gave a (4:1) diastereomeric mixture of homopropargylic methyl ethers 86 in 73% and 94% ee (Scheme 36).…”
Section: Organosilane Reagents As Carbon Nucleophilesmentioning
confidence: 99%
“…47 In addition to the two aforementioned studies, Ogasawara and Takahashi reported a catalytic asymmetric methodology to synthesize chiral allenylsilanes (Scheme 27, Table 43). 48 Table 44). 49 The presence of the silyl moiety was shown to be crucial; cyclohexyl derivative 128 provided the highest yields of cross-over product presumably due to steric factors.…”
Section: Siliconmentioning
confidence: 99%
“…To overcome this, we employed a chirality transfer from an allenylsilane. [22][23][24][25] Requisite allenylsilane 19 was prepared in an optically active form via an asymmetric reduction of a ketone under Noyori transfer hydrogenation conditions [26][27][28][29] and an S N 2′ reaction with a Lipshutz reagent. 30) Treatment of allenylsilane 19 with paraformaldehyde in the presence of TiCl 4 ·2THF afforded homopropargyl alcohol 20 in 52% yield.…”
Section: -21)mentioning
confidence: 99%